UV PHOTOCATALYSIS AND METAL DOPED TITANIUM DIOXIDE: ELIMINATION OF E. COLI AND S. AUREUS IN WATER - MOHAMED, NUR AQILAH NABILAH; WAN MANSOR, WAN SALIDA (Universiti Malaysia Terengganu Journal of Undergraduate Research, 2022)
Photocatalysis has been widely used for water disinfection and wastewater treatment. UV photocatalysis induced bacteria photocatalytic disinfection, focusing on mechanisms in bacteria inactivation. The problem with industrial wastewater is that it generally contains a high concentration of toxic or non-biodegradable pollutants. The application of photocatalysis is mainly focused on the removal of microorganisms. Metal-doped TiO2-based photocatalyst has a significant potential for the inactivation of harmful pathogens. In this research, the effect of different metal-doped on photocatalytic disinfection against Escherichia coli (E. coli) (gram-negative) and Staphylococcus aureus (S. aureus) (gram-positive) under UV light was investigated. TiO2 was used and doped with various types of metal such as copper (Cu), cobalt (Co), and iron (Fe). The experiments were run under UV light with 1 g/L of selected metal-doped for up to 3 hours. A series of photocatalytic disinfection on E. coli and S. aureus were conducted on water contamination with 500 mL of trypticase soy broth (TSB) and 5 ml of bacteria. These results show that the UV photocatalyst with Cu doped-TiO2 gives 99% of E. coli disinfection. While for S. aureus disinfection Co-doped-TiO2 gives 96% of removal bacteria after 3 hours of treatment. In conclusion, a metal-doped TiO2–based UV photocatalytic system is highly recommended for improving the water decontamination process.